2006
DOI: 10.1113/expphysiol.2006.034629
|View full text |Cite
|
Sign up to set email alerts
|

The effects of face cooling on the prolactin response and subjective comfort during moderate passive heating in humans

Abstract: The purpose of the present study was twofold: first, to determine the extent to which elevated skin temperature is responsible for the hormonal and perceptual responses to passive heating; and second, to determine to what extent face-cooling can override the effects of raised skin temperature. Sixteen recreationally active, non-heat-acclimated volunteers (12 male, 4 female; age, 29 ± 9 years, [mean ± S.D.]) underwent a passive heat exposure for 60 min in a sauna maintained at 58 • C (13% relative humidity), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 30 publications
3
32
2
1
Order By: Relevance
“…Therefore, selective cooling of a small area (180 cm 2 ) and the size of the thermal stimulus in the range of 16-17°C in hot conditions (40°C) combined with moderate eff ort did not have a signifi cant infl uence on the change in the temperature of the interior of the body. No signifi cant changes in this physiological indicator are consistent with the observations of other authors [7,14,15]. The total sweat loss based on body weight measurements (without the necessity to take into account the amount of fl uid absorbed) showed a tendency to lower water loss after cooling.…”
Section: Subjective Indicators Of Thermal Comfort and Workloadsupporting
confidence: 81%
See 3 more Smart Citations
“…Therefore, selective cooling of a small area (180 cm 2 ) and the size of the thermal stimulus in the range of 16-17°C in hot conditions (40°C) combined with moderate eff ort did not have a signifi cant infl uence on the change in the temperature of the interior of the body. No signifi cant changes in this physiological indicator are consistent with the observations of other authors [7,14,15]. The total sweat loss based on body weight measurements (without the necessity to take into account the amount of fl uid absorbed) showed a tendency to lower water loss after cooling.…”
Section: Subjective Indicators Of Thermal Comfort and Workloadsupporting
confidence: 81%
“…Previous studies suggest that cooling of the head area in warm conditions has a particular impact on subjectively assessed whole-body thermal comfort [14,15]. This is due to the fact that the head area is relatively heat sensitive, i.e.…”
Section: Selection Of the Methods Of Selective Coolingmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in heart rate with heat stress was consistent with previous findings. 18 Researchers have shown that during heat stress, peripheral vascular resistance is reduced and blood volume shifts from the central body to the periphery to facilitate heat exchange. 19 The increase in heart rate is compensatory to avoid a large drop in mean arterial blood pressure so cardiac output can be maintained even with a reduced stroke volume.…”
Section: Cardiovascular Responsesmentioning
confidence: 99%